Integrating Modular Construction, Interlocking Blocks, and Robotic Technology with Lean Principles to Improve Masonry Construction Efficiency - Karl Keyrouz; Yuxiang Chen; Farook Hamzeh (Buildings)
Current construction site conditions and practices often lead to various forms of waste, which in turn decreases productivity and value generation. Lean principles aim to minimize waste while maximizing value. However, optimizing construction flow, especially in masonry construction, remains challenging due to skilled labour shortages and rising material costs. This study developed a framework to identify and mitigate inefficiencies and reduced productivity in current construction practices. Utilizing simulation modelling, various interventions and lean scenarios were evaluated to test their effectiveness. Among the interventions evaluated, the combination of modular construction, interlocking blocks, and robotic technology yielded the most significant improvement. The results validate the potential of integrating lean practices and robotic technology to enhance productivity and efficiency in masonry construction.